A detailed evaluation of charge recombination dynamics in dye solar cells based on starburst triphenylamine dyes. Issue 1 (22nd November 2017) - Vinayak, Manikkedath V.; Yoosuf, Muhammed; Pradhan, Sourava C.; Lakshmykanth, Thyagarajan M.; Soman, Suraj; Gopidas, Karical R.
Abstract : Molecularly engineered starburst triphenylamine dyes, endowed with better hole separation and structural effects preventing recombination leading towards improved efficiencies. Abstract : Understanding the charge transfer dynamics in dye solar cells (DSCs) is imperative for the development of highly efficient devices. The loss in photocurrent due to recombination can be alleviated by removing holes formed in the oxidized dye molecules away from the TiO2 surface and also by preventing the oxidized species in the electrolyte from coming near the semiconductor. Focusing on elucidating these two parameters we fabricated I − /I3 − electrolyte based dye solar cells with two novel branched propeller shaped triphenylamine dyesTPAA4 andTPAA5 with broader absorption and higher molar extinction coefficient, which showed power conversion efficiencies of 6.52% and 4.60% respectively. The bulkiness of the co-donor along with the triple bond bridges provided further rigidity to the structure, thereby reducing aggregation of the dyes on the TiO2 surface. Both the dyes were structurally engineered in such a way to avoid the recombination of electrons from TiO2 . Detailed charge transfer dynamics of the devices were studied by employing extensive perturbation techniques such as electrochemical impedance spectroscopy (EIS), charge extraction (CE) and intensity-modulated photovoltage spectroscopy (IMVS).